The meeting with the other in Jean-Paul Sartre - Gonçalves, Aline Ibaldo (2013)
Through the look starts the relationship with the Other. In Being and Nothingness, Sartre uses the example of shame as a way of being of consciousness which the other arises as a mediator of The Self with itself, because I feel ashamed of myself as I appear to the others. There is a connection between me and the other, different from my relationship with objects.When I am seen, I'm aware of me, but I am not my own foundation, I have my foundation outside myself through the others. By the look, I live the alienation of my possibilities, because the other transforms me into an object. By being objectified, I get an externality as if I had an essence. But man does not have access to this essence. The existence and the freedom of others threaten me, because I stay immobilize in the being-in-itself. However, I do not coincide with what others apprehend of me, because I cannot look at me like the other looks. It will always be indecipherable to me. But, anytime I can return the other’s look, thus, putting myself in my own freedom confronting the other.